PERKEMBANGAN NASIONALISME DI ASIA TENGGARA - Elsha Putriany Br Girsang; Angel Sinambela; Yeza Pebina Kaban; Ririn Eriva Tampubolon; Muhammad Annoer Rafiq; Raja Pangihutan Simangunsong; Muhammad Ihsan Syahaf Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines how nationalism developed in Southeast Asia by examining the background to its emergence, the driving factors, and the formation of nation-states in several countries, including the Philippines, Myanmar, Indonesia, Indochina, and the Malay Peninsula. In this region, nationalism emerged as a response to Western colonialism, which influenced politics, economics, society, and culture. Using a descriptive-qualitative approach based on literature, this research demonstrates the differences in nationalist movements influenced by the social structure, education, and colonial dynamics in each country. The results of this study confirm that nationalism in Southeast Asia has specific characteristics in each country, but is generally driven by injustices resulting from colonialism, advances in modern education, and the rise of national consciousness in the early 20th century.